State Appellate Court Adaptation to Caseload Increase, 1968-1984: (United States) - Marvell, Thomas ([Verlag nicht ermittelbar], 1988)
This data collection examines the impact of caseload pressures on both intermediate appellate courts and supreme courts for each state in the nation. The data describe in detail the changes made by appellate courts and supply information related to each change. These changes include (1) adding judges, law clerks and staff attorneys, (2) expanding or creating intermediate appellate courts, (3) reducing panel size, (4) using summary procedures, (5) curtailing opinion practices by deciding cases without opinion or unpublished and memo opinions, and (6) curtailing oral argument length.